The Role of Teachers in Developing Student Profiles Pancasila At Mts Al Irsyad Pontianak - Yuliananingsih M.; Novianty, Fety; Uswatun Hasanah, Sitti (UNIVERSITAS PGRI PONTIANAK, 2025)
The purpose of this study is to find out the role of teachers in developing Pancasila Student Profiles at MTs Al Irsyad Pontianak. The methods used in this study are qualitative methods, with the form of descriptive research, and the data collection techniques are direct communication techniques and documentation techniques. Based on the results of the study, it shows that the role of teachers in the Development of Pancasila Student Profiles has been implemented. The role of teachers in developing the Pancasila Student Profile in schools is very important because teachers are direct guides and examples in shaping student character. Because the teacher plays the role of; role models, facilitators, motivators, guides, directs, and drives multicultural education and applies in learning, creating an inclusive and democratic environment, encouraging engagement in social activities, evaluation and value reinforcement.